Pengaruh Kepenatan Kerja Dan Kepuasan Kerja Terhadap Keinginan Berpindah Pada Karyawan 3second Cabang Malang - Ervita Ayu Astika; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to analyse the simultaneous and partial effect of work fatigue and job satisfaction on the desire to move on employees 3Second Malang Branch. A total of 40 samples were determined using the saturated sampling method. A quantitative approach with a descriptive research type is used to formulate research data from closed questionnaires—data analysis methods using multiple regression analysis. The study's results found that job fatigue and job satisfaction simultaneously significantly affected the desire to change. During the partial effect, work fatigue has a positive and significant impact on the desire to move, but it produces a negative but insignificant effect on job satisfaction. Keywords: work fatigue, job satisfaction, desire to change